2021
DOI: 10.1159/000520250
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Stimulation Testing Patterns Contribute to Sex Differences in Pediatric Growth Hormone Treatment

Abstract: Introduction: Males are twice as likely as females to receive pediatric growth hormone (GH) treatment in the United States, despite similar distributions of height z-scores in both sexes. Male predominance in evaluation and subspecialty referral for short stature contributes to this observation. This study investigates whether sex differences in GH stimulation testing and subsequent GH prescription further contribute to male predominance in GH treatment. Methods: Retrospective chart review was conducted of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Disparities are seen with GHST, with more White males proceeding with the test than minority groups and females ( 37 ). These studies also highlight the high proportion of females not being assessed for SS; this is distressing as SS can be the only physical examination finding in patients with Turner Syndrome ( 38 , 39 , 42 , 44 , 45 ). Grimberg et al.…”
Section: Health Disparity In Pediatric Endocrinologymentioning
confidence: 99%
“…Disparities are seen with GHST, with more White males proceeding with the test than minority groups and females ( 37 ). These studies also highlight the high proportion of females not being assessed for SS; this is distressing as SS can be the only physical examination finding in patients with Turner Syndrome ( 38 , 39 , 42 , 44 , 45 ). Grimberg et al.…”
Section: Health Disparity In Pediatric Endocrinologymentioning
confidence: 99%
“…5 Additionally, it has been shown that a male predominance exists among those who undergo growth hormone provocative testing (GH PT), the primary test in many centres to exclude GHD; and this appears to be related to the male predominance in paediatric GHD treatment in the United States. 6 Moreover, more boys than girls worldwide also receive growth hormone (GH) therapy for various indications which include both GHD and non-GH deficient states. 7,8 Societal bias and parental willingness to accept short stature more in girls could also be responsible for the sex disparity in GH therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Patients born small for gestational age (SGA) nearly reached their target height SDS after 8 years of rhGH therapy as shown in Figure 2 [31][32][33]. There was a male preponderance in our study cohort of 61%, which may be a consequence of factors previously identified to contribute to sex disparity in rhGH treatment such as: screening bias by primary care physician, referal bias to pediatric endocrionologists for evaluation, bias of acceptable height cutoffs and interpretation of GH testing results, as well as bias related to prescribing and starting GH treatment [34]. Strengths of this study include duration, completeness and comprehensiveness of individual follow-up data.…”
Section: Discussionmentioning
confidence: 65%